Antioxidants Activity and Color Evaluation of Date Fruit of Selected Cultivars Commercially Available in the United States. (21st June 2015) - Al-Jasass, Fahad Mohammed; Siddiq, Muhammad; Sogi, Dalbir S.
Abstract : Dates ( Phoenix dactylifera L.) are nutrient-rich fruit consumed throughout the world, either directly or in several food products. Six commercially available date cultivars in the US were analyzed for total phenolics, antioxidant activity using ABTS, DPPH, FRAP, and ORAC assays, and instrumental color. Total phenolics content varied from 33 to 125 mg GAE/100 g dry weight, with the highest in Barni (Saudi Arabia). Antioxidant values as determined by the ABTS in Deglet Nour (Algeria), Deglet Nour (California), Deglet Noor (Tunisia), Shahia (Tunisia), Barni (Saudi Arabia), and Khudri (Saudi Arabia) were 1300, 1047, 796, 452, 776, and 341 μ mol TE/g dry weight, respectively. Antioxidative properties as measure by DPPH, FRAP, and ORAC varied from 3.27 to 3.54, 3.29 to 5.22, and 189 to 243 μ mol TE/g dry basis, respectively. Fruit and pulp color of Deglet Nour (Algeria) was lighter whereas pulp of Barni (Saudi Arabia) was the darkest. Antioxidant values varied with different techniques used and also followed a different pattern than that of phenolics content.